Three-Dimensional visualization reconstruction assisted in the treatment of retroperitoneal liposarcoma: a case report - Ren, Xiangxiang; Xie, Tianhao; Liu, Litao; Jin, Xiaoshi; Zhang, Meng (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical efficacy of three-dimensional visualization reconstruction (3DVR) in surgical planning for complex retroperitoneal liposarcoma (RLS), we report a case of a 64-year-old female patient presenting with a mass posterior to the spleen. CT/MRI revealed a retro-splenic mass, later pathologically confirmed as dedifferentiated liposarcoma. 3D reconstruction precisely delineated a 12 × 6.0 cm tumor with three splenic feeding vessels, enabling preoperative simulation of an en bloc resection combined with splenectomy. Gross total resection (R0 resection) was achieved, and pathology confirmed no splenic invasion. No recurrence was observed during 6-month follow-up.ConclusionCompared to 2D imaging, 3D reconstruction improved stereoscopic assessment of tumor-vessel-organ relationships, reducing intraoperative uncertainty. Challenges in retroperitoneal soft-tissue contrast were mitigated using advanced segmentation. The technique enhances surgical precision, lowers operative risks, and may improve recurrence-free survival. Integration with virtual reality could further optimize preoperative planning, advocating its adoption in complex abdominal oncology.